Repurchase decision for music products in Taiwan: physical versus online media. Issue 4 (12th June 2017) - Wu, ChienHsing; Tao, Yu-Hui; Lin, Yu-Min
Abstract : Purpose: Consumer behaviors in internet are changing over time. The purpose of this paper is to propose and examine a research model that describes the repurchase behavior for the legal and paid music products of physical genre and online genre. The consumption value theory is used to develop the research model. Comparison of physical genre with online genre is presented. Implications and suggestions are addressed. Design/methodology/approach: The research model is examined empirically. The research targeted music product consumers who had purchasing experience in the past one year. The research results are obtained, and the findings are revealed on the basis of 728 valid music product consumers. Findings: The functional, emotional and epistemic value are the significant driving factors, though it shows a limited distinction for the two types. In comparing of the concepts of designed functional value, physical music consumers tend to have a stronger enthusiasm in music consumption. Social value and conditional value are not the predicators of repurchase satisfaction, implying that the music consumption is self-oriented for any normal amusement. The epistemic value shows significant on all levels of significance for the physical type, whereas insignificant if a = 0.01 for the type of online. Originality/value: The research model is applied for the two contrariety product types, and to make a comparison, trying to understand the reasons why music fans are still willing to spend money on music products and what factors make them choose between product genres. After fluctuation and alternation of the music industry within this decade, this research provides a reference and correlated results for the future studies for the related studies, especially for the prosperous physical parallel imports items and online music.